VIEWS OF SERVICE PROVIDERS ON SERVICES RENDERED TO PEOPLE WITH DISABILITIES AND ON THE NEED FOR FAMILY PRESERVATION SERVICES - Strydom, Marianne (Social Work/Maatskaplike Werk, 2015)
The article reflects the research findings of a study that was initiated because a welfare organisation delivering social work services to people with disabilities was investigating the possibility of developing a family preservation programme. The aim of the investigation was to explore the views of service providers on services delivered to persons with disabilities to determine the need for family preservation services. It was found that limited people power and funds placed serious constraints upon services. However, a clear link between the aims of family preservation and the needs of families caring for a relative with a disability has been established.